Masterpiece - Broach, Elise; Murphy, Kelly, 1977- (New York : Holt/Christy Ottaviano Books, 2008)
After Marvin, a beetle, makes a miniature drawing as an eleventh birthday gift for James, a human with whom he shares a house, the two new friends work together to help recover a Durer drawing stolen from the Metropolitan Museum of Art.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal starred, October 2008.
Notable/Best Books (A.L.A.), January 2009.
Book Links (A.L.A.), January 2009.
Pub Weekly, August 2008.
Keywords: Durer, Albrecht, -- 1471-1528 -- Juvenile fiction; Durer, Albrecht, -- 1471-1528 -- Fiction; Artists -- Juvenile fiction; Beetles -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Art thefts -- Juvenile fiction; Families -- New York (State) -- New York -- Juvenile fiction; Artists -- Fiction; Art thefts -- Fiction; Family life -- New York (State) -- New York -- Fiction; Mystery and detective stories; Beetles -- Fiction; Human-animal relationships -- Fiction; Theft -- Fiction; Family life -- Fiction; Mystery and detective stories; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; Mystery fiction